Local Corticosteroids for Alopecia Areata: A Narrative Review - Samantha Gregoire; Basil McIntosh; Katherine Sanchez; Ursula Biba; Arash Mostaghimi (Dermatology and Therapy)
Abstract Alopecia areata (AA) is an autoimmune condition of non-scarring hair loss that affects 2% of the population worldwide. Topical and intralesional (IL) corticosteroids are the two most commonly used treatments for AA. These locally acting glucocorticoid derivatives are thought to treat AA by reducing the CD8+ T-cell-mediated immune attack on hair follicles. Topical corticosteroids are safe and well tolerated with moderate efficacy in mild AA, but recurrence is common after treatment cessation. They are recommended for children and adults with mild AA who cannot tolerate IL injections. IL steroids are more effective than topical steroids given their ability to penetrate the dermis, where the hair follicle resides. Success rates are higher than topical steroids in mild-to-moderate AA. IL steroids are safe and well tolerated; however, treatment is limited by pain during the procedure. Further research is needed on ideal treatment regimens, long-term safety, preferred candidates, and the role of combination therapy to further elucidate the role of local corticosteroids for AA in clinical practice.